The Aesthetic and Ideological Dimensions: A Study of Bare Poems by Hussein Mardan - Ali Hassan Hadhili, Prof. Dr. (lark, 2025)
In late 199, the poet Hussein Mardan published his poetry collection Bare Poems, which ignited a storm of criticism and protest. The government ordered the book’s confiscation and prosecuted the poet. A committee of prominent literary figures was formed to assess the collection, and it concluded that the content did not constitute a criminal offense. As a result, the court decided to release both the poet and his book. This introduction highlights the significance of Bare Poems as a pivotal early moment in modern Iraqi poetry. While poets such as Badr Shakir al-Sayyab and Nazik al-Malaika had already begun pioneering new poetic forms, Mardan’s collection remained loyal to the traditional form, but not to its moral and ideological content. This study focuses on the aesthetic and ideological dimensions within the collection, based on the premise that a balanced relationship between the two is essential for poetic integrity. When ideology overwhelms aesthetics, it can damage the poetic text. Bare Poems serves as a clear example of such damage, where the ideological burden paralyzed poetic vision rather than elevating it to its deserved artistic stature. The research is divided into an introduction and two main sections. The first explores ideological expression in the works of various poets, while the second investigates the aesthetic dimension within Mardan’s collection amid an atmosphere heavily charged with ideology searching, perhaps, for glimpses of artistic merit.